A female perspective on Christianity and modernity: Maude Petre (1863–1942) and the history of Catholic Modernism. Issue 4 (2nd October 2022) - Marotta, Giulia
ABSTRACT: In spite of a large and diverse body of research on the topic, the relationship between Christianity and modernity is still an open question and a nodal point for our understanding of Western civilization. This paper aims at providing an original contribution to this debate by bringing into play the impact of gender-related views and practices. In particular, it focuses on Catholic Modernism, and analyzes this phenomenon and its repression by the Vatican hierarchy from the understudied perspective of female historiography by way of an exemplary case study: the life and work of Maude Petre. Maude Petre (1863–1942) was a British Roman Catholic, member of a female religious community, a leading figure of Catholic Modernism, and one of its first historians. Because of the long-term patterns of gender imbalance which shaped the Catholic establishment and milieu, Petre's position as an active female modernist intellectual gave her a truly unique perspective on the confrontation between tradition and change within Western Christianity. Her work offers an outstanding opportunity to revise existing definitions of Catholic Modernism, while also opening new avenues to interpret the religious entanglements of the Western intellectual tradition at large.